Investigating the psychometric properties of the Patient Health Questionnaire for Adolescents (PHQ-A) and Center for Epidemiologic Studies - Depression Scale for Children (CES-DC) among young adolescents in South Africa - Mirriam Mkhize; Claire van der Westhuizen; Katherine Sorsdahl (PLoS ONE, 2025)
Depression among adolescents is a global concern, including in South Africa, emphasizing the need for reliable screening tools. While the the Patient Health Questionnaire Adolescent (PHQ-A) and Center for Epidemiologic Studies - Depression Scale for Children (CES-DC) are commonly used mental health screening tools among adolescents, their psychometric properties in South Africa are not well-studied. This study aims to fill this gap by examining the psychometric properties of the PHQ-A and CES-DC among adolescents aged 10–14-year-olds in South Africa. First, a sample of 42 adolescents aged 10–14 years were recruited to participate in cognitive testing focus groups to determine their comprehension of the depression screening tool items. Secondly, a sample of 500 adolescents from 10 schools completed a tablet-based survey including socio-demographic information and the adapted depression screening tools. A subset of 123 adolescents underwent clinical diagnostic interview with the MINI-KID depression modules only. After two weeks, a subset of 145 adolescents had the initial tablet-based survey re-administered for test-retest reliability. Criterion validity was examined using ROC analysis, with the MINI-KID as the reference standard. Of the 500 adolescents surveyed, the majority were female (59.2%), with an average age of 12 years (SD = 1.42). The PHQ-A demonstrated good internal consistency (alpha = 0.82) and moderate test-retest reliability (ICC = 0.56). The CES-DC showed good internal consistency (alpha = 0.86) and moderate test-retest reliability (ICC = 0.68). The PHQ-A displayed good sensitivity (85.7%) and specificity (61.8%). Youden’s index indicated 7.5 as the ideal cutoff score for the PHQ-A. The CES-DC has a sensitivity of 95.2% and specificity of 56.9% and Youden’s index of 21. Factor structure for the PHQ-A included one factor loading for 9 items and 3 factor loading for 8 items; while for the CES-DC factor structure consisted of o three factor loadings. The findings show good psychometric properties of the PHQ-A and CES-DC and contributes to the limited research on mental health assessment tools for younger adolescents in Africa. Testing the psychometric properties of the PHQ-A and CES-DC for this population could help improve early detection and intervention for mental health conditions.